Paraneoplastic Pemphigus: A Striking Complication of Undiagnosed Lymphoma - Blake O. Adnani; Kathleen O’ Brien; Zaw W. Myint; Brandon L. Adler (Case Reports in Hematology)
A 49-year-old male with no past medical history presented with acute-onset painful mucosal erosions along with flaccid bullae on his trunk, scalp, and intertriginous areas. The patient initially underwent a skin biopsy which demonstrated suprabasilar acantholysis and lichenoid interface dermatitis. This was followed by a computed tomography scan which identified a large abdominal lymph node. Core needle biopsy of this node demonstrated follicular lymphoma. Lastly, indirect immunofluorescence (IIF) in rat bladder was positive (titer 1 : 10,240). This finding confirmed the diagnosis of paraneoplastic pemphigus (PNP) in the setting of follicular lymphoma. The patient’s cutaneous disease was treated with a combination of intravenous immunoglobulin and methylprednisolone, along with intravenous rituximab, with a resolution of his cutaneous symptoms. His lymphoma was treated with six cycles of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R–CHOP), with an interval decrease in his tumor burden. PNP is an autoimmune-mediated mucocutaneous disease associated with underlying neoplasm, most commonly non-Hodgkin lymphoma or chronic lymphocytic leukemia. Affected patients develop variable autoantibodies to antigens on keratinocytes and the basement membrane zone. Severe intractable stomatitis is characteristic, in addition to polymorphous cutaneous eruptions including bullae and erosions. Mortality rates can reach up to 90% due to malignancy, sepsis, or bronchiolitis obliterans, an irreversible and often lethal cause of pulmonary insufficiency. We highlight PNP manifesting in a patient with lymphoma, who responded well to the skin- and malignancy-directed treatments. PNP is an exceedingly rare diagnosis that should be considered in a patient with intractable stomatitis.